2012
DOI: 10.1021/jm300623u
|View full text |Cite
|
Sign up to set email alerts
|

3-Oxoisoindoline-1-carboxamides: Potent, State-Dependent Blockers of Voltage-Gated Sodium Channel NaV1.7 with Efficacy in Rat Pain Models

Abstract: The voltage-gated sodium channel Na(V)1.7 is believed to be a critical mediator of pain sensation based on clinical genetic studies and pharmacological results. Clinical utility of nonselective sodium channel blockers is limited due to serious adverse drug effects. Here, we present the optimization, structure-activity relationships, and in vitro and in vivo characterization of a novel series of Na(V)1.7 inhibitors based on the oxoisoindoline core. Extensive studies with focus on optimization of Na(V)1.7 potenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 45 publications
2
26
0
1
Order By: Relevance
“…C-fiber nociceptors have long been known to encode pain and hyperalgesia [ 50 ], and our results support existing data showing that C-fiber nociceptors have a strong role in driving the pain of formalin and CFA. Electrophysiological studies in vivo have shown that C- and Aδ-fiber nociceptors both are sensitized following CFA [ 51 , 52 ], and the effects of compound 52 on C-fibers are consistent with previous experiments using a selective peptide inhibitor of Nav1.7 [ 53 ] and with effects of a small molecule Nav1.7 inhibitor on ectopic firing of injured sensory nerves [ 33 ]. Neither the spontaneous nor the evoked responses of C-fiber nociceptors were completely prevented by compound 52.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…C-fiber nociceptors have long been known to encode pain and hyperalgesia [ 50 ], and our results support existing data showing that C-fiber nociceptors have a strong role in driving the pain of formalin and CFA. Electrophysiological studies in vivo have shown that C- and Aδ-fiber nociceptors both are sensitized following CFA [ 51 , 52 ], and the effects of compound 52 on C-fibers are consistent with previous experiments using a selective peptide inhibitor of Nav1.7 [ 53 ] and with effects of a small molecule Nav1.7 inhibitor on ectopic firing of injured sensory nerves [ 33 ]. Neither the spontaneous nor the evoked responses of C-fiber nociceptors were completely prevented by compound 52.…”
Section: Discussionsupporting
confidence: 76%
“…A role for Nav1.7 in inflammation-induced pain is consistent with existing literature, in that this channel is increased in sensory ganglia following inflammation [ 30 ] and in painful human dental pulp [ 31 ], and mice with genetic deletion of Nav1.7 in a subset of neurons exhibited reduced responses to inflammation-induced pain [ 32 ]. In sum, data presented here support the hypothesis that pharmacological inhibition as well as genetic deletion of Nav1.7 may alleviate multiple forms of pain [ 6 , 7 , 33 , 34 ], and that either the formalin or CFA model in rats is an appropriate driver assay for the development of future Nav1.7 inhibitors.…”
Section: Discussionsupporting
confidence: 76%
“…Data from animal models of inflammatory and neuropathic pain have suggested that ralfinamide exhibits a significant analgesic effect while also having a well-tolerated safety profile [6,7,8]. Moreover, ralfinamide is the only small molecule drug in a late-stage clinical trial for the treatment of neuropathic pain [9,10,11,12,13]. However, the anti-allodynic efficacy and Nav1.7-selectivity of ralfinamide need further improvement.…”
Section: Introductionmentioning
confidence: 99%
“…This moiety can be found in a number of biologically active natural compounds and synthetic derivatives as well [ 5 , 6 , 7 ]. As a special subgroup, isoindolin-1-ones bearing a carboxylic ester or carboxylic amide function ( 2 ) may show anticancer- [ 5 ], antiarrhythmic- [ 8 ] or sodium channel modulator activities [ 9 ]. It is known that phosphorus analogues of biologically active carboxylic acid derivatives may often show important effects, e.g., α-aminophosphonates and α-amino acids [ 10 ].…”
Section: Introductionmentioning
confidence: 99%